How wages respond to shocks: asymmetry in the speed of adjustment - Tairi R\~o\~om; Aurelijus Dabusinskas (European Central Bank (ECB), 2011)
The time series of various economic variables often exhibit asymmetry: decreases in the values tend to be sharp and fast, whereas increases usually occur slowly and gradually. We detect signs of an analogous asymmetry in firms' wage setting behaviour on the basis of managerial surveys, with employers tending to react faster to negative than to positive shocks in the same variables. As well as describing the presence of asymmetry in the speed of wage adjustment, we investigate which companies are more likely to demonstrate it in their behaviour. For this purpose, we apply the Heckman selection model and develop a methodology that improves identification by exploiting heteroscedasticity in the selection equation. The estimation results imply that companies operating in a more competitive environment have a higher propensity to react asymmetrically. We also find that businesses relying on labour-intensive production technology are more likely to react faster to negative shocks. Both of these findings support the hypothesis that this behaviour results from companies' attempts to protect profit margins.
Keywords: J30; J31; J33; 330; Asymmetry; survey; wage dynamics; Wage setting